MWASTools: an R/Bioconductor package for metabolome-wide association studies - Rodriguez,Martinez A; Posma,JM; Ayala,R; Neves,AL; Anwar,M; Petretto,E; Emanueli,C; Gauguier,D; Nicholson,JK; Dumas,M (Bioinformatics, 2017)
Summary: MWASTools is an R package designed to provide an integrated pipeline to analyze metabonomic data in large-scale epidemiological studies. Key functionalities of our package include: quality control analysis; metabolome-wide association analysis using various models (partial correlations, generalized linear models); visualization of statistical outcomes; metabolite assignment using statistical total correlation spectroscopy (STOCSY); and biological interpretation of MWAS results.Availability: The MWASTools R package is implemented in R (version > =3.4) and is available from Bioconductor: https://bioconductor.org/packages/MWASTools/